Effectiveness of the EM 2R3SW Digital Application on Parental Outcomes for Childhood Leukemia Prevention: A Quasi- Experimental Study in Depok, Indonesia - Ratumas Ratih Puspita; Rizki Handayani Fasimi; Rafika Dora Wijaya; Rohanah Rohanah; Rita Dwi Pratiwi (STIKep PPNI Jawa Barat, 2025)
Background: Childhood acute lymphoblastic leukemia (ALL) is a leading cause of cancer-related morbidity and mortality in low- and middle-income countries, including Indonesia. Parental gaps in knowledge, attitudes, preventive behaviors, and healthy lifestyle practices contribute to delayed detection and poor outcomes. Digital health platforms offer scalable strategies to strengthen preventive health literacy in families. Objective: To evaluate the effectiveness of EM-2R3SW, a web-based digital education application, on parental knowledge, attitudes, preventive behaviors, and healthy lifestyle practices related to childhood leukemia prevention. Methods: A quasi-experimental pretest–posttest study was conducted among mothers of children aged 0–18 years in Sukmajaya District, Depok, Indonesia (N = 112). Participants accessed leukemia-prevention multimedia content within EM-2R3SW over two weeks. Validated questionnaires measured outcomes at baseline and post-intervention. Data were analyzed using Wilcoxon signed-rank tests due to non-normal distribution (Kolmogorov–Smirnov p < 0.05). Results: Significant improvements were observed across all outcomes. Knowledge scores increased from 16.48 to 27.65, attitudes from 68.15 to 85.95, preventive behaviors from 72.39 to 112.20, and healthy lifestyle practices from 68.39 to 109.27 (all p < 0.001). Category transitions demonstrated marked progression from inadequate to good–very good levels, particularly in preventive practices. Conclusion: The EM-2R3SW digital intervention effectively improved parental literacy and behavioral determinants for childhood leukemia prevention. This approach is feasible, low-cost, and scalable for community-based cancer prevention efforts in resource-limited settings. Larger randomized studies with long-term follow-up are recommended